Strategi optimalisasi program dana desa melalui pemberdayaan masyarakat dalam perspektif ekonomi Islam - Dian Rahmawati; Muhammad Mujtaba Mitra Zuana; Muawanah (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2020)
The village fund provides a very important position for the village to carry out development and community empowerment programs. These include programs for the welfare of the community. Village funds have an important role in improving the economy of rural communities, with effective and efficient use and allocation. This study uses field research with descriptive research methods, the methods used in this study are: observation, structured interviews, and documentation. After the researchers have collected data, the next step is to do the data analysis. The analysis conducted by researchers uses two ways, namely processing the initial data and classifying it and then the next stage of the data will be analyzed. Based on the results of this study it can be concluded that the management of village funds in the village of Kemiri has been running in accordance with existing technical guidelines, so that the development in the village of Kemiri from the existence of village funds has brought considerable changes starting from improving infrastructure facilities, educational advice, health facilities etc. but in the field of empowerment in the village of Kemiri is still not optimal this is due to the lack of community participation in the management of village funds. In the field of development and empowerment, the community is only involved in planning and implementation, but in terms of accountability and evaluation of the community village fund program, it has not been directly involved.